Pombalia barbata, a new species of Violaceae endemic to the Brazilian Caatinga - de Paula-Souza, Juliana; Souza, Vinicius Castro (Phytotaxa, 2015)
A new species of Pombalia Vand. (Violaceae) is described and illustrated. Pombalia barbata Paula-Souza is endemic to caatingas from Ceará to northern Minas Gerais states in Brazil, and is distinguished from other species of the genus by its bearded style. Further distinctive features and comments about its relationships with morphologically related species P. attenuata and P. communis are provided, as well as discussions on geographical distribution.